Receivers in American Football Use a Constant Optical Projection Plane Angle to Pursue and Catch Thrown Footballs. (August 2013) - Shaffer, Dennis M; Dolgov, Igor; Maynor, Andrew; Reed, Cody
In the present work we test how well two interceptive strategies, which have been proposed for catching balls hit high in the air in baseball and cricket, account for receivers in American football catching footballs. This is an important test of the domain generality of these strategies as this is the first study examining a situation where the pursuer's locomotor axis is directed away from the origin of the ball, and because the flight characteristics of an American football are far different from targets studied in prior work. The first strategy is to elicit changes in the ball's lateral optical position that match changes in the vertical optical position so that the optical projection plane angle, ψ, remains constant, thus resulting in a linear optical trajectory (LOT). The second is keeping vertical optical ball velocity decreasing while maintaining constant lateral optical velocity (generalized optical acceleration cancellation, or GOAC). We found that the optical projection plane angle was maintained as constant significantly more often than maintaining vertical and lateral optical velocities as GOAC predicted. The present experiment extends previous research by showing that the constancy of ψ resulting in an LOT is used by humans pursuing American footballs and demonstrates the domain generality of the LOT heuristic.